Deoxynivalenol inhibits the expression by goblet cells of intestinal mucins through a PKR and MAP kinase dependent repression of the resistin‐like molecule β. Issue 6 (27th April 2015) - Pinton, Philippe; Graziani, Fabien; Pujol, Ange; Nicoletti, Cendrine; Paris, Océane; Ernouf, Pauline; Di Pasquale, Eric; Perrier, Josette; Oswald, Isabelle P.; Maresca, Marc
<x xml:space="preserve">Abstract</x> Scope The food‐associated mycotoxin deoxynivalenol (DON) is known to affect intestinal functions. However, its effect on intestinal mucus is poorly characterized. Methods and results We analyzed the effects of DON on human goblet cells (HT29‐16E cells) and porcine intestinal explants. Results showed that subtoxic doses of DON (as low as 1 μM) decreased mucin (MUC) production. qPCR analysis demonstrated that this inhibition was due to a specific decrease in the level of mRNA encoding for the intestinal membrane‐associated (MUC1) and the secreted MUCs (MUC2, MUC3). Mechanistic studies demonstrated that DON effect relied on the activation of the protein kinase R and the mitogen‐activated protein kinase p38 ultimately leading to the inhibition of the expression of resistin‐like molecule beta, a known positive regulator of MUC expression. Conclusion Taken together, our results show that at low doses found in food and feed, DON is able to affect the expression and production of MUCs by human and animal goblet cells. Due to the important role of MUCs in the barrier function and in the interaction of commensal bacteria with the host, such effect could explain the observed modifications in the microbial diversity and the increased susceptibility to enteric infection following exposure to DON.